Virus from the Global South: A comparative analysis on Twitter commentary on China x Covid-19, and South Africa x Omicron - Rabin, Fadiyah (Centre for Film and Media Studies, 2024)
On the 12th of March 2020, the World Health Organisation (WHO) declared the widespread outbreak of Covid-19 a pandemic. This announcement came after months of monitoring a cluster of cases in Wuhan, China, in 2019 and led to a series of global lockdowns and travel restrictions to inhibit the spread of the virus. China and WHO were blamed by some for the spread of the virus for not raising concerns sooner. The combination of blame and Covid-19 misinformation led to increased xenophobia toward people of Asian descent. Nearly two years later, in November 2021, variant B.1.1.529 was discovered in South Africa. This variant was named Omicron and is considered a variant of concern by the WHO. In response, various countries from the Global North initiated travel bans for several southern African countries. Despite initial cases only being identified in South Africa and Botswana, southern African countries were being unfairly punished due to South Africa's transparency and the efforts of their scientists. These responses reinforce colonial perceptions of Africa and Asia as a ‘county of illness' (Shim, 1998; Flint & Hewitt, 2015; Lee, 2017; Kagumire, 2021). Commentary on these events were widely discussed and shared on Twitter. Twitter allows for broader commentary on current events as user posts (Tweets) reflect their perspectives and contributions to any debates that may be ongoing. Drawing on an analysis of the most shared (retweeted) posts from two datasets, this thesis conducts a comparative content analysis to identify dominant themes. Datasets were collected over 7-days, starting from the dates of WHO's announcements on the widespread outbreak of Covid-19 being declared a pandemic (2020), and the Omicron variant being declared a variant of concern (2021a). From these datasets, 3000 (1500 x 2) of the top retweeted tweets were analysed through qualitative content analysis. This thesis explores whether the online conversations reinforce stereotypes surrounding historical perceptions of China and Africa. Furthermore, the thesis explores whether the data sets revealed broader commentary on geopolitical tensions that were potentially heightened during the pandemic. Findings showed that although the datasets did not reveal many instances of explicit hate speech, there was discussion highlighting racial stigma and racial scapegoating of both China and South Africa. Both datasets also showcased broader commentary on geopolitical tensions, specifically centred around influence, power, and 6 inequality. These discussions drew on the ongoing battle for global power between the US and China and how the pandemic highlighted existing divides between the Global North and Global South. Stemming from colonial differentiations between “primitive” and “advanced”, the phrase “Global South” is a contested term. However, the term has shifted from its focus on development and culture to geopolitical power relations (Connell & Dados, 2012). Lastly, both datasets showcased how Twitter can be used by citizens as a tool to challenge and critique power elites.